Jellyfish Lakes at Misool Islands, Raja Ampat, West Papua, Indonesia - GANDI Y.S PURBA; EKO HARYONO; SUNARTO SUNARTO; JEMMY MANAN; LUKAS RUMENTA; PURWANTO PURWANTO; LEONTINE E. BECKING (Society for Indonesian Biodiversity, 2018)
Purba GYS, Haryono E, Sunarto, Manan J, Rumenta L, Purwanto, Becking LE. 2018. Jellyfish Lakes at Misool Islands, Raja Ampat, West Papua, Indonesia. Biodiversitas 19: 172-182. Misool Islands, located in southern Raja Ampat in West Papua, has dozens of anchihaline lakes (marine lakes). Three of these lakes, Lenmakana, Karawapop, and Keramat, house populations of jellyfish. This study mapped and described the characteristics of the three ‘jellyfish lakes’ during field surveys in October 2015 and May 2016. The lakes ranged in area from 0.5?3.2 hectares. All three lakes harbored Mastigias papua, Lenmakana and Keramat lakes also harbored Aurelia sp., and Keramat had a third jellyfish species Cassiopea ornata. However, at Karawapop the jellyfish were not found on the water surface during the first round of field work because of effects associated with the El Niño phenomenon at that time. As a result of the El Niño effect, at Keramat, brown Mastigias became white in May 2016. The three lakes have different tidal delays (30?120 min) and dampened tidal amplitude (62%) compared to the sea. The benthos was found to be dominated by bivalves (Brachidontes sp.), algae (Cladophora sp., or Halimeda sp.) and sponges (predominantly Haliclona spp. and Tethya spp.). In addition, species of the family Synaptidae (Holothuroidea) were abundant and spread over almost all the bottom of Karawapop Lake, while tube-worms of the Polychaeta class were identified in Keramat Lake. Although these lakes are identified as a conservation area, currently there is no management activity in Lenmakana and Karawapop Lakes, despite the fact that the lakes are growing in popularity as a tourist site. Our paper provides the baseline data for future conservation efforts.